STUDY TENTANG KEPUASAN PELANGGAN DAN MINAT MEMBELI ULANG - Ma'mun, Muhammad; Widiyanto, Ibnu; Mudiantono, Mudiantono (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2014)
The purpose of this research was to test the influences of employee hospitality, SPBU image,complete fascility toward customer satisfaction to increase rebuying intention. The usage ofthese variables was able to solve the arising problem within SPBU Alvia Brother’s SampangMadura.The samples of this research consisted of a hundred customers on SPBU Alvia Brother’sSampang Madura. The analysis technique used here is multiple regression with the leastsquare difference and hypothesis test using t-statistic to examine partial regression coefficientand f-statistic to examine the mean of mutual effect with level of significance 5%. In addition,classical assumption was also performed including normality test, multicolinearity test, andheteroscedasticity test.The result of the analysis showed that employee hospitality, SPBU image, complete fascilityan positive influence, which is significant to customer satisfaction and rebuying intention. Theempirical result indicated that to increase rebuying intention of SPBU Alvia Brothers SampangMadura, management need to pay attention on factors like employee hospitality, SPBU image,and complete fascility, because that is the factors that effect high or low level of rebuyingintention.